2003
DOI: 10.1189/jlb.0403177
|View full text |Cite
|
Sign up to set email alerts
|

Specific CD4 down-modulating compounds with potent anti-HIV activity

Abstract: Despite the availability of the current clinically approved anti-HIV drugs, new classes of effective antiviral agents are still urgently needed to combat AIDS. A promising approach for drug development and vaccine design involves targeting research on HIV-1 entry, a multistep process that comprises viral attachment, coreceptor interactions, and fusion. Determination of the viral entry process in detail has enabled the design of specific agents that can inhibit each step in the HIV entry process. Therapeutic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 104 publications
1
22
0
Order By: Relevance
“…22 Similar reduction of CD4 expression was observed in other T-cell lines (i.e., SupT1, MOLT-4, CEM, and Jurkat), in freshly isolated blood lymphocytes and monocytes, in monocytic cell lines (i.e., THP-1 and U937) and in CD4 transfected cells (i.e., U87, A2.01 and C3.2). 19,20 Time course experiments revealed that CD4 downmodulation by CADA differs in its mechanism of action from aurintricarboxylic acid, which binds to CD4, and phorbol myristate acetate, which activates protein kinase C. 22 CD4 mRNA levels are not affected by CADA, suggesting that CD4 expression is not inhibited at a transcriptional level. Despite its superficial structural resemblance to bicyclams, 16,23 CADA does not inhibit HIV replication by simply binding to a cell surface receptor or coreceptor and preventing the interaction of gp120 with the receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Similar reduction of CD4 expression was observed in other T-cell lines (i.e., SupT1, MOLT-4, CEM, and Jurkat), in freshly isolated blood lymphocytes and monocytes, in monocytic cell lines (i.e., THP-1 and U937) and in CD4 transfected cells (i.e., U87, A2.01 and C3.2). 19,20 Time course experiments revealed that CD4 downmodulation by CADA differs in its mechanism of action from aurintricarboxylic acid, which binds to CD4, and phorbol myristate acetate, which activates protein kinase C. 22 CD4 mRNA levels are not affected by CADA, suggesting that CD4 expression is not inhibited at a transcriptional level. Despite its superficial structural resemblance to bicyclams, 16,23 CADA does not inhibit HIV replication by simply binding to a cell surface receptor or coreceptor and preventing the interaction of gp120 with the receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Viral entry inhibitors are actively being pursued as novel anti-HIV agents, [11][12][13] including anti-CD4 antibodies 14,15 and chemokine receptor antagonists. 16,17 Multiple domains of CD4 are involved in the viral entry process; 18 therefore, downregulation of the complete CD4 receptor 19,20 may be considered a more effective method for CD4 blocking in the treatment of HIV infections. Antisense oligonucleotides have been demonstrated to partially reduce lymphocyte surface CD4 expression.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that the lead compound CADA specifically decreases surface CD4 in several types of human CD4 ϩ cells (i.e., T lymphocytes, monocytes, and dendritic cells), producing broad-spectrum antiviral potency against infection by laboratory HIV strains and clinical isolates belonging to various clades, independent of tropism (37)(38)(39)41). The compound does not directly interact with gp120 or cell surface CD4; it specifically decreases cellular biosynthesis of CD4 (unpublished data).…”
mentioning
confidence: 99%
“…One such cohort consists of individuals with a mutation in both alleles for the CCR5 receptor. CCR5 was identified as one of the receptors used by the virus for entry and is now target of intense research on entry inhibitors, a novel class of drugs (Vermeire and Schols, 2003).…”
Section: Discussion Spontaneous Regressionsmentioning
confidence: 99%